Galileo against circular inertia (Scientiae Studia, 2005)
According to the scholars who propound 'circular inertia' as one of the main aspects of Galileo's conceptual frame, the Italian pioneer of modern physics believed that only circular motions around the center of a cosmic body like the Earth could persist without action of a force. This widely accepted interpretation is based upon excerpts from the two Galileo's masterpieces, the 1632 Dialogue and the 1638 Discorsi. Those scholars, nevertheless, do not take into consideration other passages from those books in which Galileo's words do not fit their interpretation. These passages will be brought to light in order to reject the 'circular inertia' interpretation and in order to support the viewpoint that Galileo's concept of inertia does not take into account the path of a motion, but deals solely with the "degree of speed indelibly impressed" on a moving body.